Medical Law as a Separate Area of Law - K. A. Gavrilenko (Здоровье мегаполиса, 2023)
Existence of medical law as a separate area of law in the legal system of the Russian Federation is considered. This article will be helpful in determining the legal basics of medical law, as well as scientific and historical aspects of its development.